Tryptophan metabolism: Mechanism-oriented therapy for neurological and psychiatric disorders - Li, Dan; Yu, Shuang; Long, Yu; Shi, Ai; Deng, Jie; Ma, Yin; Wen, Jing; Li, Xiaoqiu; Liu, Songyu; Zhang, Yulu; Wan, Jinyan; Li, Nan; et al. (Frontiers in Immunology, 2022)
Neurological and psychiatric disorders are a category of chronic diseases that are widespread and pose serious mental and physical health problems for patients. The substrates, products, and enzymes of Tryptophan metabolism all contribute to the development of neurological and psychiatric disorders. This paper deals with three metabolic pathways of tryptophan that produce a series of metabolites called tryptophan Catabolics (TRYCATs). These metabolites are involved in pathological processes such as excitotoxicity, neuroinflammation, oxidative stress, and mitochondrial damage and are closely associated with neurological and psychiatric disorders such as Alzheimer's disease and depression. Here, we review the elements that affect how tryptophan metabolism is regulated, including inflammation and stress, exercise, vitamins, minerals, diet and gut microbes, glucocorticoids, and aging, as well as the downstream regulatory effects of tryptophan metabolism, including the regulation of glutamate (Glu), immunity, G-protein coupled receptor 35 (Gpr35), nicotinic acetylcholine receptor (nAChR), aryl hydrocarbon receptor (AhR), and dopamine (DA). In order to advance the general understanding of tryptophan metabolism in neurological and psychiatric disorders, this paper also summarizes the current situation and effective drugs of tryptophan metabolism in the treatment of neurological and psychiatric disorders and considers its future research prospects.